PENGARUH LEVERAGE, PROFITABILITAS,TIPE INDUSTRI, DAN KEPEMILIKAN MANAJEMEN TERHADAP PENGUNGKAPAN CORPORATE SOSIAL RESPONBILITY - Gde Sathya Narendra (Jurnal Manajemen dan Bisnis, 2015)
Given the importance of Corporate Social Responsibility (CSR), the issue which is ofparticular interest are the factors that influence it, among others, leverage, managementownership, industry type and profitability. Otherwise in Manufacture Company in Bursa EfekIndonesia an effort to Corporate Social Responsibility (CSR, have noticed leverage,management ownership, industry type and profitability.The formulation of the problem in this research is : whether leverage influence toprofitability, whether management ownership influence to profitability, whether industry typeinfluence to profitability, whether leverage influence to Corporate Social Responsibility (CSR),whether industry type influence to Corporate Social Responsibility (CSR) and whetherprofitability influence to Corporate Social Responsibility (CSR). However, to answer theproblem, we conducted research with secondary data by www.idx.com. The analysis techniqueused is Structural Equation Model (SEM) AMOS Version 20.Based on the results obtained conclusions include : there is negative significant influencebetween leverage to profitability, there is significant influence between management ownershipto profitability, there is significant influence between industry type to profitability, there isnegative significant influence between leverage to Corporate Social Responsibility (CSR),there is significant influence between industry type to Corporate Social Responsibility (CSR)and there is significant influence between profitability to Corporate Social Responsibility(CSR).Keyword : leverage, management ownership, industry type, profitability and CorporateSocial Responsibility (CSR)